1992 : the external dimension - Henderson, David (New York : Group of Thirty, 1989)
This paper considers some possible effects of completion by the end of 1992 of the Single Market within the European Community. These effects are viewed from the standpoint of countries outside the Community and Market
osc 11/03/2019
Loans
Keywords: Economic Intergration